2017
DOI: 10.1136/archdischild-2016-312104
|View full text |Cite
|
Sign up to set email alerts
|

Abstention or intervention for isolated hypotension in the first 3 days of life in extremely preterm infants: association with short-term outcomes in the EPIPAGE 2 cohort study

Abstract: In this population, antihypotensive treatment was associated with improved short-term outcomes. Therapeutic abstention should be cautiously considered for early isolated hypotension in extremely premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 27 publications
2
39
1
5
Order By: Relevance
“…The incidence of BPD based on disease severity was reported in four data sources from Europe [31][32][33]43,45,49,51], three from North America [77,[88][89][90], and one from Asia [106]. Moderate BPD was defined as a requirement for <30% supplemental oxygen to maintain target oxygen saturation levels; severe BPD was defined as a requirement for !30% supplemental oxygen or positive pressure ventilation to maintain target levels.…”
Section: Incidence Of Bpd By Severitymentioning
confidence: 99%
“…The incidence of BPD based on disease severity was reported in four data sources from Europe [31][32][33]43,45,49,51], three from North America [77,[88][89][90], and one from Asia [106]. Moderate BPD was defined as a requirement for <30% supplemental oxygen to maintain target oxygen saturation levels; severe BPD was defined as a requirement for !30% supplemental oxygen or positive pressure ventilation to maintain target levels.…”
Section: Incidence Of Bpd By Severitymentioning
confidence: 99%
“…Many neonatologists therefore consider low arterial blood pressure not as an indication for urgent medical intervention, if a baby is otherwise stable 8–10. However, experience in adults, children, and several observational studies in preterm infants3–6 11 12 promote a different approach with early volume replacement and intravenous application of catecholamines to prevent prolonged hypotension. As of yet, no large-scale randomised controlled trials of catecholamine treatment in preterm infants have been published 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine is more effective than dobutamine at increasing blood pressure in hypotensive infants, although dobutamine or epinephrine may be a more rational choice in the setting of reduced ventricular function [174]. Randomised trials exploring thresholds for intervention with inotropes have been unsuccessful due to poor recruitment; however, a recent observational study showed that preterm infants treated for isolated hypotension, defined as mean arterial pressure less than gestational age, had a higher survival rate raising caution about “permissive hypotension” [175]. Hydrocortisone is also a reasonable choice for extremely preterm infants with hypotension, particularly those with documented low serum cortisol [176, 177].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%